Investigation of the biochemical effects of renin inhibition in normal volunteers treated by an ACE inhibitor. - Chauveau, D (1992)
1. In order to investigate accurately the biochemical effects of renin inhibition in man, we have developed a sensitive assay to measure angiotensin I (1-10) decapeptide. 2. Angiotensins were extracted from plasma by adsorption to phenylsilylsilica, and angiotensin I (Ang I) was quantified by radioimmunoassay. The detection limit was 0.77 fmol ml-1, and the extraction recovery of [125I]-Ang I added to albumin buffer was 83% at the inflection point (10 fmol ml-1) of the standard curve. The overall recovery was 98.5 +/- 3.5%. The intra- and inter-assay reproducibility was 10.4% and 9.7% respectively. Cross-reactivity of the antiserum used was low (less than 0.3%) with all angiotensin peptides tested except Ang (2-10) nonapeptide. 3. A human pharmacological model was subsequently used to assess in vivo the biochemical effects of the renin inhibitor CGP 38560A. Six healthy volunteers received 20 mg lisinopril, a long-acting ACE-inhibitor. During the following 24 h, the renin-angiotensin system was reset with typically elevated active plasma renin and Ang I, at respectively 275 and 429% of basal values. 4. In a randomized three-way cross-over protocol, the six volunteers received a 30 min infusion of the renin inhibitor CGP 38560A (125 or 250 micrograms kg-1) or 5% glucose. The fall in plasma Ang I was 92% and 97.5% after the lowest and highest dose of the renin inhibitor, respectively. A concomitant increase in active plasma renin was observed.(ABSTRACT TRUNCATED AT 250 WORDS)